Priming effects on soil organic carbon decomposition induced by high C:N crop inputs - Mazzilli, Sebastián; Piñeiro, Gervasio; Kemanian, Armen (Agrociencia Uruguay, 2012)
Carbon budgets in soils can be computed by a simple equation in which inputs are accounted by the humification of residues added to the soil, and outputs are estimated by the respiration of soil organic carbon (CS). It is generally accepted that physical protection in soil aggregates and chemical recalcitrance limit the rate of CS decomposition. We propose that soybean-based crop sequences will have lower steady state CS stocks than those based on corn, because of lower C inputs and enhanced soil respiration of CS due the so-called priming effect. To address this hypothesis, we studied CS turnover from δ13C natural abundance changes in no-till corn and soybean crops. Soybean and corn crops were sown with a complete randomized design with three replicates on an old pasture with an intermediate soil δ13C signal of -16.34. Soils were sampled at the beginning and after two years of continuous no till cropping. Aboveground and belowground C inputs were measured each year for corn and soybean crops. Soil and plant samples were analyzed for C, nitrogen and 13C/12C ratio. Corn C inputs where significantly higher than soybean (10.7 and 7.0 Mg ha-1), but no significant changes in CS where observed among treatments (68 Mg ha-1 in the first 0.3 m). However, the Cs turnover and humification rates under corn (0.015 and 0.18 y-1) were higher than under soybean (0.006 and 0.11 y-1). Contrary to our predictions high C:N corn residues enhanced CS decomposition, but also the stabilization of fresh residues into CS, suggesting that soil microbes mine the soil organic matter while feeding on high C:N crop residues. Possible explanations for such result are discussed.